Evaluating the physical-mechanical properties of flowable fiber-reinforced and bulk-fill Giomer composites: a comparative study of advanced technologies - Obeid, Alyssa Teixeira; López, Arnaldo José Capellán; Forcin, Letícia Vendrametto; Brondino, Nair Cristina Margarido [UNESP]; Mondelli, Rafael Francisco Lia; Raymundo, Sofia Furlanete [UNESP]; Alhotan, Abdulaziz; Silikas, Nick; de Amoêdo Campos Velo, Marilia Mattar [UNESP] (Frontiers, 2025)
The mechanical performance and polymerization shrinkage stress of resin composites play a critical role in maintaining marginal integrity over time. This in vitro study compared the properties of fiber-reinforced flowable resin (FRC) and S-PRG bulk-fill flowable resin composites. Three materials were tested: EVER X (FRC), S-PRG (Giomer tecnology), and SDR (conventional bulk-fill). Analyzed variables included surface hardness (SH), depth of cure, flexural strength (FS), modulus of elasticity (E), polymerization shrinkage stress, and degree of conversion (DC). Scanning electron microscopy (SEM) was employed to assess composite morphology. Samples were prepared for SH, depth of cure, and DC measurements. A three-point bending test evaluated FS and E, while shrinkage stress was measured between parallel steel plates. A strong positive correlation was found between FS and E. S-PRG exhibited the highest shrinkage stress, followed by EVER X and SDR. SEM images of fractured EVER X samples showed fiber-pulling effects, indicating internal reinforcement. EVER X demonstrated superior mechanical properties-including high flexural strength, surface hardness, degree of conversion, and elastic modulus-making it a promising option for load-bearing restorations. S-PRG, with its excellent depth of cure, may be more suitable for situations requiring deeper light penetration.